Determination and Removing of Mercury from Heavy Crude Oil by Extraction with Aqueous solutions - Muhawee, Eptessaam; Abid Uon, Abdul Husain; Hamed, Shaimaa; Abd Al-Hadee, Eman; Redi, Asmaa (Iraqi Journal of Science, 2023)
Mercury can have significant impact on petroleum and related industries, it is also known to poison catalysts used in refining processes.Wet ash methods was widely used in determination of mercury in crude oil but the elemental and organic mercury are volatile and losses are also expected .An investigation of the use of Aqueous solution to prevent loss of mercury during wet digestion resulted in consistently good recoveries from crude oil samples.In this research diluted aqueous solution of sodium polysulfide is used and the parameters studied are polysulfide aqueous solution concentration, time, and ratio of the aqueous solution to crude oil,and will take different forms of heavy crude oil from several fields and the previous measurement of mercury both ways( wet ash) and new (aqueous) and compare the results. The results show that the procedure is reproducible and comparable in accuracy to other establish procedures.